The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2050312119845715
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in polypharmacy in persons with dementia: A scoping review

Abstract: Purpose: To date, research studies in most disciplines have not made sex-based analysis a priority despite increasing evidence of its importance. We now understand that both sex and gender impact medication prescribing, use, and effect. This is particularly true for older adults with dementia who have alterations in drug metabolism, drug response, and the permeability of the blood–brain barrier. To better understand the influence of sex and gender on drug use in older adults with dementia, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
1
12
0
1
Order By: Relevance
“…We found direct comparative literature in only two indicators: absence of anticholinergic medication and assessment of functional status. Our finding that men had less frequent use of anticholinergic medication was consistent with two studies [36,37], but inconsistent with others which found no significant difference in anticholinergic use between men and women with dementia [38,39]. In terms of functional status assessments, our study was consistent with one other study [40], which found hospitalized older women had more assessments than older men (9.1% of men did not have an assessment recorded, compared to 8.0% of women).…”
Section: Resultssupporting
confidence: 66%
“…We found direct comparative literature in only two indicators: absence of anticholinergic medication and assessment of functional status. Our finding that men had less frequent use of anticholinergic medication was consistent with two studies [36,37], but inconsistent with others which found no significant difference in anticholinergic use between men and women with dementia [38,39]. In terms of functional status assessments, our study was consistent with one other study [40], which found hospitalized older women had more assessments than older men (9.1% of men did not have an assessment recorded, compared to 8.0% of women).…”
Section: Resultssupporting
confidence: 66%
“…However, consistent with findings from some other studies,16,32,33 in our study men were more likely than women to be prescribed with APs. A recent review by Trenaman et al34 observed that men and women tend to use more antipsychotics dependent on their living environment, women in the community and men in long-term care facilities. The review concluded further research is required to obtain more solid evidence and understand how gender differences can be used to improve medication use among patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…To test the independent association between polypharmacy and mental health, there is a need to control for a wide range of third varibles that can potentially confound such an association. The first group of potential confounders are demographic factors such as age and gender [7][8][9][10]. It has been demonstrated that polypharmacy is more common in women, and older individuals, who have a higher number of chronic diseases and frequent contact with the health care system [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The first group of potential confounders are demographic factors such as age and gender [7][8][9][10]. It has been demonstrated that polypharmacy is more common in women, and older individuals, who have a higher number of chronic diseases and frequent contact with the health care system [7][8][9][10]. At the same time, depressive symptoms are also more common in women than men [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%